2020
DOI: 10.3389/fimmu.2020.00061
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocyte-Mediated Liver Immunopathology of Schistosomiasis

Abstract: The parasitic worms, Schistosoma mansoni and Schistosoma japonicum, reside in the mesenteric veins, where they release eggs that induce a dramatic granulomatous response in the liver and intestines. Subsequently, infection may further develop into significant fibrosis and portal hypertension. Over the past several years, uncovering the mechanism of immunopathology in schistosomiasis has become a major research objective. It is known that T lymphocytes, especially CD4 + T cells, are essential for immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 154 publications
0
101
0
2
Order By: Relevance
“…Excessive Th1 polarization, however, is detrimental to the host, as seen in IL‐4 and IL‐4/IL‐10 double–deficient mice which had a higher mortality than wild‐type mice infected with S mansoni 23,28 . The shift to the chronic Th2 granulomatous response in S mansoni infections is considered to be driven by toxic elements of the soluble egg antigens (SEA), 41 and only recently has an analogous S japonicum SEA compound been identified 42 . Cells recruited to the granuloma primarily include neutrophils, eosinophils, monocytes, lymphocytes and epithelioid cells 29 .…”
Section: Composition Of the Granulomamentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive Th1 polarization, however, is detrimental to the host, as seen in IL‐4 and IL‐4/IL‐10 double–deficient mice which had a higher mortality than wild‐type mice infected with S mansoni 23,28 . The shift to the chronic Th2 granulomatous response in S mansoni infections is considered to be driven by toxic elements of the soluble egg antigens (SEA), 41 and only recently has an analogous S japonicum SEA compound been identified 42 . Cells recruited to the granuloma primarily include neutrophils, eosinophils, monocytes, lymphocytes and epithelioid cells 29 .…”
Section: Composition Of the Granulomamentioning
confidence: 99%
“…T cells are essential for both the generation of granulomas and for the cellular composition of the granuloma, with some differences apparent between the schistosome species 41,77 . During early experiments, it was observed that granulomas in S mansoni ‐infected hamsters showed a lymphoid periphery in addition to the initial eosinophil rich infiltration and epithelioid cell centre 19 .…”
Section: Composition Of the Granulomamentioning
confidence: 99%
“…japonicum infected mice, CD3e −/− B6 mice were found completely deprived of peripheral T cells in blood and spleen ( Fig 1A, 1B and 1C ). As T cells participate in tissue damage during infection [ 14 ], it was not surprising for us to find that the liver granuloma of CD3e −/− B6 mice which were deprived of T cells was visible but apparently alleviated when it was compared to granuloma in infected WT control mice ( Fig 1D ). However, it is interesting to note that the worm development was significantly affected by CD3e deficiency, with 1.2-fold decrease in worm width which was quantitated based on digital micrographs, while the length of the worm recovered from WT mice and CD3e deficient mice exhibited no significant differences ( Fig 1E, 1F and 1G ).…”
Section: Resultsmentioning
confidence: 98%
“…Recent clinical advances in immunotherapy, preventing T cell exhaustion, boosting T cell activation or releasing T cell tolerance mechanisms, have led to striking clinical benefits in cancer treatment, demonstrating that T cells can be manipulated to respond under an immunosuppressive environment and provide protective immunity, which also suggests that T cells could be harnessed to treat persistent infections [10][11][12]. In previous studies, T cell differentiation in mice were found to be significantly modulated during schistosomiasis [13], and T cells are involved in immunopathology including liver fibrosis [14]. However, infection experiments still lack in determining whether T cells could impact worm development and parasite load in the naturally resistant hosts, which is at least partially due to difficulties to obtain appropriate genetic models.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in our results it is possible to observe that the animals' immunization with the NDPK and ADSL enzyme within 48 days after infection showed a decrease in the percentage of granulomas in the liver and the number of eggs in the liver, when compared to the infected/untreated group, showing higher percentages of reduction to NDPK. The decrease in the number of eggs is very important, once granulomas are caused mainly by immune responses against soluble egg antigens (SEAs) (37), and even a smaller number of eggs being deposited in the tissues can lead to a reduction in the process granulomatous (38), consequently considering a possible decrease in the morbidity of this pathogenesis. Our findings are in accordance with the study by Neris et al (39), where the authors observed that PNP and HGPRT, enzymes of the metabolic pathways of nucleotides, were able to modulate the infection by reducing the parasitic load on the liver, intestine and feces from animals infected with S. mansoni after 48 days of infection.…”
Section: Discussionmentioning
confidence: 99%